The Impact Of Electronic Word Of Mouth And Digital Payment On Electronic Business Applications - Ghauri, Pervez N.; Salzberger, Thomas (Yayasan Pendidikan Belajar Berdikari, 2023)
With the advancement of technology and information, many company sectors now use technology and media as a tool in marketing. Advertising development has become a contemporary trend for achieving long-term corporate performance. However, issues develop when the firm chooses the improper social networking platforms, resulting in a detrimental influence on the company itself. The purpose of this research is to look into the impact of electronic word of mouth and digital payment convenience on purchasing decisions made on the OLX application in Pangandaran Regency. In this study, 111 people were chosen at random to use an online shopping application on their smartphone. In this study, a multiple linear regression analysis strategy utilizing SPSS software version 26 is applied. The findings indicate that electronic word of mouth and digital payment variables have an impact on purchase intent and can be classified as positive.